Review on class imbalance techniques to strengthen model prediction - Putta, Hemalatha; Amalanathan, Geetha Mary (Institute of Advanced Engineering and Science, 2025)
Data is a fundamental component in various fields, including science, business, health care, and technology. It is often processed, stored, and analyzed using computer systems and software applications. The importance of data lies in its ability to provide valuable insights, drive innovation, and improve decision-making processes. However, it’s essential to handle and manage data responsibly to address privacy and ethical considerations. Data mining (DM) involves discovering patterns, trends, correlations, or useful information from large datasets. Data dredging or DM and machine learning (ML) are closely related fields that both involve the analysis of data to discover patterns and make predictions. DM focuses on extracting knowledge from data; ML emphasizes the development of algorithms that can do analysis. The two fields are interconnected, and the techniques from one state of art integrated into the processes of the other. In ML the class imbalance problem occurs due to the class distribution in the training data is not equal. Imbalanced classification refers to a condition where a particular class (minority class) is under represented parallelled to another class (majority class) in a dataset. This paper furthermore emphasizes on the synthetic minority oversampling technique (SMOTE) variants employed by the researchers, and highlights the limitations the work.